Composite storage systems for compressed hydrogen - systematic improvement of regulations for more attractive storage units. (7th May 2020) - Mair, G.W.; Becker, B.; John, S.; Duffner, E.
Abstract: Hydrogen is an attractive energy carrier that requires high effort for safe storage. For ensuring safety, they must undergo a challenging approval process. Relevant standards and regulations for composite cylinders used for the transport of hydrogen and for its on-board storage are currently based on deterministic (e.g. ISO 11119-3) or semi-probabilistic (UN GTR No. 13) criteria. This paper analysis the properties of such methods with respect to the evaluation of load cycle strength. Their characteristics are compared with the probabilistic approach of the BAM. Based on Monte-Carlo simulations, the available design range (mean value and scatter of strength criteria) of current concepts was exemplarily estimated. The aspect of small sample sizes is analysed and discussed with respect to the evaluation procedures. Highlights: The safety level of approval requirements is assessed by simulation of populations. Production scatter needs to get part of safety assessment of composite cylinders. In case of high scatter unsafe composite cylinders may currently get approved. Assessment of populations show gaps in safety dependent from production scatter. This performance analysis of regulations provides an efficient improvement.